1990
DOI: 10.1177/036354659001800405
|View full text |Cite
|
Sign up to set email alerts
|

Lateral release of the patella: Indications and contraindications

Abstract: Charts were reviewed on patients at the Salt Lake Knee and Sports Medicine Clinic who had had a lateral release of the patella. Patients were divided into two groups. Group I contained patients who were entirely satisfied with the procedure, and Group II included patients who were complete failures (defined as a need for further surgical procedures). In Group I, 74 patients were included in the subjective followup. Forty of the 74 patients also had an objective followup, including roentgenograms and a physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
0
8

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 299 publications
(134 citation statements)
references
References 10 publications
1
125
0
8
Order By: Relevance
“…35 Our findings indicate that it was subjects with a positive patellar tilt test that responded favorably to medial glide taping. Presumably, individuals with a positive patellar tilt have a flexible lateral retinaculum.…”
Section: Predictors Of Intervention Successmentioning
confidence: 56%
See 2 more Smart Citations
“…35 Our findings indicate that it was subjects with a positive patellar tilt test that responded favorably to medial glide taping. Presumably, individuals with a positive patellar tilt have a flexible lateral retinaculum.…”
Section: Predictors Of Intervention Successmentioning
confidence: 56%
“…The patellar tilt test was originally described as a convenient clinical measure to determine if a patient has a tight lateral retinaculum. 35,65 Kolowich et al 35 proposed that an excessively tight lateral retinaculum is identified by the inability of the examiner to lift the lateral border of the patella above the true horizontal plane (with the patient supine and relaxed and knee in full extension). If the lateral border of the patella can be Nomogram showing the pretest probability of intervention success using patellar taping (52%), and the improved posttest probability (83%) for intervention success after applying the clinical prediction rule.…”
Section: Predictors Of Intervention Successmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency and complexity of clinical problems has led to a wide range of surgical procedures 1 that address joint geometry, 2,3 skeletal alignment, [4][5][6][7] or the soft tissues. 8,9 Little data are available providing objective information about the effects of these factors on patellar tracking or relationships to symptoms. 10 Patellar ''maltracking'' implies that the patella is not following a normal stable path of movement, within the femoral trochlear groove, when the knee is flexing-extending.…”
Section: Introductionmentioning
confidence: 99%
“…Both the knee with patellar dislocation (dislocated group) and the contralateral knee without patellar dislocation (non-dislocated group) were investigated. No patient in this series had a hypermobile patella that was defined abnormal medial and lateral laxity in the patellar glide test [22].…”
Section: -1 Patients and Control Subjectsmentioning
confidence: 85%